Finding the Right Fit: How (and Why!) Academic Libraries can Support Trades Education - Guffroy, Leah; Verbeem, Jeff (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2025)
Although a current trend in education emphasizes the importance of developing job-ready graduates in skilled trades, in librarian circles there has been little attention paid to our role in this movement. This article explores perspectives from two trades librarians on this gap in the context of postsecondary institutes. We find that while many academic libraries and librarians may be under-prepared to support many of their campus’s trades programs, there are opportunities for librarians to come together in support of one another. Remarking on our experiences, we share reflections from others in the community and discuss what needs to be done to meet a growing need for student support.